Interface entre história da matemática e ensino: uma atividade desenvolvida com base num documento do século XVI - Saito, Fumikazu; Dias, Marisa da Silva [UNESP] (Universidade Estadual Paulista (Unesp), Faculdade de Ciências, 2013)
Este artigo propõe a construção de uma interface entre história e ensino de matemática a partir de um diálogo entre historiadores e educadores da matemática. Para tanto, consideramos aspectos epistemológicos e metodológicos ligados à história da matemática, pautada em tendências historiográficas atuais, juntamente com a metodologia baseada no movimento lógico-histórico. A interface contemplou o movimento do pensamento na formação dos conceitos e o contexto no qual tais conceitos foram desenvolvidos, de modo a conduzir à reflexão sobre o processo histórico da construção do conhecimento para a elaboração de atividade didática. Esta atividade teve por base um documento do século XVI dedicado à construção e uso de instrumentos matemáticos, e sua elaboração levou em consideração uma intencionalidade e um plano de ação que viabilizaram o seu desenvolvimento. A organização do ensino articulou as conexões internas e externas trazidas pela análise do documento e a forma do pensamento do desenvolvimento do conceito.

This paper proposes to devise an interface between history and mathematics education based on a dialogue between historians of mathematics and educators. Regarding this, we have considered epistemological and methodological aspects of the history of mathematics based on current trends in historiography along with the methodology based on the logic-historical approach. The interface sought to envisage the movement in thought in the context in which these very concepts were conceived and the context in which mathematical concepts were developed. This interface led us to reflect on the historical process of development of knowledge by which a didactic activity could be devised. This activity was based on a sixteenth century document devoted to the construction and use of mathematical instruments. Activity elaboration took into account an intention and a plan of action through which its application was made possible. The teaching organization took into consideration the internal and external connections brought about by analysis of the document and the thought form in developing the concept.
An interface between the history of mathematics and education: an activity based on a sixteenth-century document
Keywords: História da matemática; Ensino de matemática; Atividade didática; History of Mathematics; Mathematics teaching; Didactic activity